Identifikasi Miskonsepsi Menggunakan Three-Tier Diagnostic Test Berbasis Google Form pada Pokok Bahasan Potensial Listrik - Eka Maryam (LP4MK STKIP PGRI Lubuklinggau, 2020)
The purpose of this study was to identify misconceptions by using the Google Form-based Three-Tier Diagnostic Test on a potential electrical subject. The type of misconception in question is conceptual misunderstandings or wrong conceptual understanding. This research uses descriptive research with a quantitative approach. This research was conducted in the Computer System Engineering Program of Bina Insan Lubuklinggau University. Data collection techniques using multilevel multiple-choice diagnostic tests, the reason for choosing answers in the form of essays or explaining concepts on the selected answers are then uploaded in jpg or pdf form and lastly the confidence level or Certainty of Response Index (CRI). Data analysis is done by looking for the percentage of misconceptions of each indicator. The results of the study obtained misconception data with an average percentage of 34% and were in the category of moderate misconceptions. The value of students who understand the concept but are not sure is 1% and the average value of students who do not understand the concept is 4%. Overall, the average value of students who understand the concept is greater than in other categories of 61%.